2015
DOI: 10.1111/nph.13479
|View full text |Cite
|
Sign up to set email alerts
|

Improved photosynthetic performance during severe drought in Nicotiana tabacum overexpressing a nonenergy conserving respiratory electron sink

Abstract: SummaryChloroplasts have means to manage excess reducing power but these mechanisms may become restricted by rates of ATP turnover. Alternative oxidase (AOX) is a mitochondrial terminal oxidase that uncouples the consumption of reducing power from ATP synthesis.Physiological and biochemical analyses were used to compare respiration and photosynthesis of Nicotiana tabacum wild-type (WT) plants with that of transgenic lines overexpressing AOX, under both well-watered and drought stress conditions.With increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 81 publications
6
64
0
Order By: Relevance
“…S2A–D). This corresponds with our previous work at 150 PPFD (Dahal et al , 2014, 2015). A similar pattern across plant lines was also evident in the 400 PPFD- and 700 PPFD-grown plants experiencing low RWC’s and measured at saturating irradiance (Supplementary Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…S2A–D). This corresponds with our previous work at 150 PPFD (Dahal et al , 2014, 2015). A similar pattern across plant lines was also evident in the 400 PPFD- and 700 PPFD-grown plants experiencing low RWC’s and measured at saturating irradiance (Supplementary Fig.…”
Section: Resultssupporting
confidence: 92%
“…However, in AOX knockdown plants a lower stress severity threshold (RWC of about 75–80%) already induced this limitation, while in AOX overexpression plants a much higher stress threshold (RWC below about 55%) was necessary to induce this limitation. These results are consistent with a model whereby the non-energy-conserving nature of AOX respiration can act to alleviate chloroplast energy imbalances, hence increasing the threshold level of drought stress necessary to induce the biochemical limitations of photosynthesis (Dahal et al , 2014, 2015; Dahal and Vanlerberghe, 2017). …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Lines with reduced AOX also showed obvious TPU and at a lower capacity than WT. The AOX appeared to help tobacco tolerate water stress (Dahal et al 2015). Without the AOX, presumably to help dissipate energy when photosynthetic electron transport was in excess, TPU limitation was induced.…”
Section: Tpu Is Normally In Slight Excess Of the Required Capacitymentioning
confidence: 99%
“…Studies in Arabidopsis and tobacco (Nicotiana tabacum) clearly revealed a role for AOX in the dissipation of excessive reducing power while maintaining photosynthesis under high-light stress (Florez-Sarasa et al, 2011Dahal et al, 2014Dahal et al, , 2015Vanlerberghe et al, 2016). In Arabidopsis, aox1a knockout plants cannot be complemented by the expression of other isogenes (Strodtkötter et al, 2009;Kühn et al, 2015).…”
mentioning
confidence: 99%